The interrelations between mathematics and philosophy in Leibniz´s thought - Goethe, Norma; Beeley, Philip; Rabouin, David (2023)
Fil: Goethe, Norma. Universidad Nacional de Córdoba. Facultad de Filosofía y Humanidades. Escuela de Filosofía; Argentina.